Wound management by using negative pressure wound therapy - Uršič, Helena; Novak, Marko (Onkologija : Slovenian Journal of Oncology, 2010)
Negative pressure wound therapy (NPWT) enhances wound healing and helps to prepare the wound for closure by reducing oedema and increasing perfusion, by removing exudate from the wound and by enhancing granulation tissue formation. The duration of treatment has no limitations and depends on the goal of therapy, wound size and pathology, and comorbidities. NPWT should be stopped when the wound is closed or ready to be closed surgically or shows no progress for one to two consecutive weeks. NPWT helps to optimize patients care and can be used in hospital or in outpatient care. There are no detailed recommendations for NPWT in oncology, decision is made individually. At the Institute of Oncology Ljubljana NPWT is used since 2007 and since then 62 wounds have been treated.